Intrastromal corneal foreign body – case series and discussion on the physics of injury - Andrea BK; Safinaz MK; Umi Kalthum Md Noh; Mushawiahti Mustapha (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Traumatic injury to the eye can occur due to various causes, most of which are avoidable. Here we report three cases of intrastromal corneal foreign bodies (FB) which required surgical removal. Most corneal FBs are removed easily at the slit lamp, however, these cases required surgical intervention due to the mechanism of which the FB penetrated into the stroma. Although the mechanism of injury was similar, with all three cases occurring at high velocity, we observed that the entry and level of penetration differed in each case. In the first case, the corneal FB penetrated the cornea and was embedded in the anterior stroma, whereas in the second case, the FB was embedded in the posterior stroma, but with an intact endothelium. In the third case, the FB caused a full thickness, self-sealed laceration wound but remained embedded in the stroma. Through further evaluation, we noted that several factors contribute towards the severity of the injury, namely, anatomy of the cornea, area affected, shape, size, mass and velocity of the object. We speak in depth about the mechanism of injury and physics associated with these injuries and why the penetration differed in each case.